PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV RISHA DESA GUGAH SEJAHTERA KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Fitriana; Wahab; Marina (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
The success of an organization is influenced by many factors, one of which is employee performance. Meanwhile, employee performance is influenced by motivation and work discipline. Problems with motivation and work discipline will impact employee performance. This study aims to examine and determine the partial and simultaneous influence of motivation and work discipline on employee performance at CV Risha, Gugah Sejahtera Village, Pemangkat District, Sambas Regency. This research is an associative study with a quantitative approach. It was conducted at CV Risha, Gugah Sejahtera Village, Pemangkat District, Sambas Regency. This study used primary data collected using a questionnaire. The researchers employed quantitative analysis using multiple linear regression and coefficient of determination analysis using SPSS 27. The population was all 41 employees of CV Risha Pemangkat, using a nonprobability sampling technique with a saturated sampling method. The results showed that motivation positively impacted employee performance, with a significance value of 0.004 < 0.05 and a calculated t-value of 3.101 > t-table of 2.024. Work discipline positively impacted employee performance, with a significance value of 0.016 < 0.05 and a calculated t-value of 2.526 > 2.024. Simultaneously, motivation and work discipline significantly impacted employee performance, with a significance value of 0.001 < 0.05. The coefficient of determination value in this study was 41.2% and the remaining 58.8% was influenced by other variables not used in this study.